A Re-Examination of the Lemma through Digital and Functional Lenses - Agerbo, Heidi (HERMES - Journal of Language and Communication in Business, 2019)
The lemma is one of the core terms in lexicography. It is the lexicographical item that users of paper dictionaries normally utilise to look for the dictionary article that can help them satisfy their information need, and lexicographers consider the lemma an essential and indispensable part of a lexicographical tool. However, as new technologies are continuously being developed and many dictionaries (or lexicographical data) are incorporated into other kinds of digital tools, e.g. writing software and e-readers, it is necessary to re-examine the notion of lemma because these changes have consequences for the definition of this term. Furthermore, research into the operative function – one of the main functions in the lexicographical function theory – has shown that the lemma should not only be associated with words, but also other types of needs than those related to linguistic signs, something which e-dictionaries more easily are able to accommodate compared to paper-based dictionaries. This contribution, therefore, re-examines the lemma and investigates its role in e-dictionaries, and it suggests a provisional definition of this core lexicographical term that is applicable in e-dictionaries and in digital tools based on lexicographical data.